Matter of Authenticity of Electronically Agreed Penalty as Similar in Writing - Ujmajuridze, Ia (Journal of Law, 2022)
The modern world is increasingly consuming the Internet in everyday life. Through the Internet, people, among others, enter into consumer contracts. This circumstance gave rise to the need to adapt the relations to the legal norms, if necessary - to introduce new legislation. In the footsteps of the development of the Internet, an electronic form of contract was created, which was similar to a simple written form of contract. In this circumstance there arises a legal question - whether the electronically agreed legal category is equal to written one. The purpose of this article is, among others, to answer this question.